Effectiveness of Storytelling Versus Lecture Methods on Oral Health Knowledge in Children Aged 7–8 Years: A Quasi-Experimental Study - Suci Rahmasari; Yona Ladyventini; Rahmi Khairan (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Dental caries remains the most prevalent chronic disease in children worldwide, disproportionately affecting school-age populations in low- and middle-income countries. This quasi-experimental study evaluated the effectiveness of storytelling versus traditional lecture methods in improving oral health knowledge among children aged 7–8 years (mean age 7.4 ± 0.5 years) in Padang, Indonesia. Methods: A total of 110 children were enrolled and assigned to storytelling (n=55) and lecture (n=55) groups, with 108 children (54 per group) completing the study. Pre-test and post-test knowledge assessments were conducted using a validated 15-item questionnaire (Content Validity Index = 0.87, Cronbach’s α = 0.73). Results: The storytelling group demonstrated a significant mean score increase of +1.28 points (95% CI: 0.97–1.59, p < 0.001, Cohen’s d = 1.12), while the lecture group showed a non-significant gain of +0.35 points (95% CI: -0.13 to 0.83, p = 0.152, Cohen’s d = 0.22). Post-intervention, 83.3% of the storytelling group achieved “good” knowledge levels compared to 51.9% in the lecture group (OR = 4.66, 95% CI: 1.88–11.54, p < 0.001; NNT = 3.2). Children with lower baseline knowledge benefited most from storytelling (r = 0.51, p < 0.010). Children perceived storytelling as more enjoyable (92.6% vs 51.9%), easier to understand (88.9% vs 59.3%), and more motivating for oral hygiene practice (81.5% vs 50.0%). Conclusion: Storytelling was significantly more effective than lectures in enhancing oral health knowledge, particularly among children with limited baseline understanding, supporting its implementation as a school-based oral health promotion strategy.